Functions of credit risk management in Non Banking Financial Institutions (NBFI) in Bangladesh : a study on IDLC Finance limited - Jabeen, Chowdhury Tasmiah (BRAC University, 2011)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2009.